Oxygen Delivery in the Adult Intensive Care Unit with a Focus on Hyperoxic Acute Lung Injury Pathogenesis and Clinical Manifestations - Zachary M. Harris; Edward P. Manning (Journal of Intensive Care Medicine, 2026)
High oxygen damages human lung, called hyperoxic acute lung injury (HALI). HALI pathogenesis involves formation of reactive oxygen species (ROS) which overwhelm antioxidant mechanisms and lead to alveolar epithelial and endothelial cell death and interstitial inflammation. Resultant alveolar flooding causes ventilation-perfusion (V/Q) mismatch, hypoxic respiratory failure, and death. 12–16 h of severe hyperoxic exposure potentiates symptoms that include substernal chest discomfort, cough, and sore throat. Alterations in pulmonary function that ensue are decreased vital capacity (VC), decreased arterial oxygen tension (PaO 2 ), increased intrapulmonary shunt, and increased dead space-to-tidal volume ratio (V D /V T ). A multitude of observational studies demonstrate harm of hyperoxic exposure in critically ill patients. While one randomized clinical trial (RCT) found targeting a lower oxygenation target in critically ill patients was beneficial compared with a higher target, another RCT demonstrated harm of such a strategy in patients with acute respiratory distress syndrome (ARDS). Multiple subsequent RCTs examining effects of lower- and higher-oxygenation strategies in critically ill patients identify no clear benefit of either strategy in the general ICU population. However, heterogeneous effects of lower- and higher-oxygenation approaches in ICU patient subgroups warrant further investigation. It is paramount that ICU physicians recognize that lethal and sublethal amounts of hyperoxia result in lung damage and that patients who require hyperoxia to avoid deleterious hypoxia can be at risk for HALI. For each patient in the ICU, it is likely that ideal oxygen targets depend on the specific medical conditions affecting the patient and is a promising area of future study.